2019
DOI: 10.1177/1359104519890905
|View full text |Cite
|
Sign up to set email alerts
|

Haemophiliac adolescents’ perspectives of resilience: A qualitative study based on the resilience in illness model

Abstract: A qualitative study was conducted to investigate the concept of resilience among Iranian haemophilic adolescents based on the Haase’s Resilience in Illness Model (RIM). Purposive sampling was used to recruit 15 participants comprising haemophilic adolescents and their parents in the study. The data were collected through in-depth semi-structured interviews and analysed using direct content analysis. The themes and categories were defensive coping (emotive coping, evasive coping), courageous coping (optimism, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The present study found a significant positive correlation between spiritual health and resilience, which is consistent with results in other diseases (depression, spinal cord injury, schizophrenia, and bipolar disorder) [ 42 , 44 , 73 ]. In addition, spirituality is often considered an important resilience resource and protective factor that can increase resilience through its impact on relationships, life values, personal meaning, and better coping with stress [ 74 , 75 , 76 ]. Jones’ study found that spiritual health, a significant predictor of resilience, explained more than half (51%) of the variance in resilience [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study found a significant positive correlation between spiritual health and resilience, which is consistent with results in other diseases (depression, spinal cord injury, schizophrenia, and bipolar disorder) [ 42 , 44 , 73 ]. In addition, spirituality is often considered an important resilience resource and protective factor that can increase resilience through its impact on relationships, life values, personal meaning, and better coping with stress [ 74 , 75 , 76 ]. Jones’ study found that spiritual health, a significant predictor of resilience, explained more than half (51%) of the variance in resilience [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the present study results, Haase et al (2014) in the RIM reported that the perceived support from family, friends, and health providers can be regarded as a significant protective factor. Additionally, previous studies indicated that social support is one of the most important predictors of resilience, high levels of which leads to an increase in resilience as a protective factor (Nourian et al, 2016; Parviniannasab et al, 2020; Thompson et al, 2018; Van der Hallen et al, 2020). This discrepancy can be attributed to the fact that in Iran, the role of family is more prominent than relatives and friends.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, this correlation was stronger for the optimistic subscale compared with the other variables. Several studies have also shown that optimism was considered as an important aspect of resilience, which had a high correlation with resilience (Nourian et al, 2016; Parviniannasab et al, 2020; Souri & Hasanirad, 2011). The RIM also indicated optimism as an important factor in resilience and as the main component of courageous coping (Haase et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations